MANAJEMEN ORGANISASI BERBASIS BUDAYA RELIGIUS DI SEKOLAH DASAR MUHAMMADIYAH 1 BANDAR LAMPUNG - Ira Ainun Zulfiah; Amiruddin Amiruddin; Ahmad Fauzan (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2024)
Education implicitly functions and aims to develop students' cognitive, affective and psychomotor personality potential. Advances in information technology have an impact, namely the easy entry of biotechnology and the infiltration of foreign culture which is negative, this can affect both the ethics, morals and character of students. So Muhammadiyah 1 Elementary School Bandar Lampung created and implemented a religious culture for all school members. The aim of this research is to determine and analyze the concept of organizational management based on religious culture at Muhammadiyah 1 Bandar Lampung Elementary School with the functions of planning, organizing, acting, evaluating in creating and cultivating religious culture in the elementary school. The approach method is descriptive with qualitative research. Data collection techniques use observation, interviews and documentation regarding records of past events or school history and others, which discuss the problems in the research. Data analysis techniques use data collection, data reduction, data presentation and drawing conclusions. The validity checking technique uses extended participation and source triangulation. The conclusions of this research are: 1) Organizational planning based on religious culture at Muhammadiyah 1 Elementary School Bandar Lampung on religious culture has gone through systematic planning stages and processes, in accordance with the vision, mission and goals of the school; 2) Organizing a religious culture-based organization at Muhammadiyah 1 Bandar Lampung Elementary School based on religious culture in the division of authority, functions, duties and responsibilities based on the school organizational structure that has existed so far; 3) Implementing (actuating) a religious culture-based organization at Muhammadiyah 1 Elementary School Bandar Lampung on religious culture during implementation on a daily, weekly and annual basis; 4) Evaluation of religious culture-based organizations at Muhammadiyah 1 Elementary School Bandar Lampung on religious culture is carried out with supervision, reporting and control.